Existence of two-dimensional physical gels even at zero surface pressure at the air/water interface: rheology of self-assembled domains of small molecules - Veschgini, Mariam; Habe, Taichi; Mielke, Salomé; Inoue, Shigeto; Tanaka, Motomu (Angewandte Chemie. International edition, 2017)
Films of mesoscopic domains self-assembled from fluorocarbon/hydrocarbon diblock copolymers (FnHm) at the air/water interface were found to display highly elastic behavior. We determined the interfacial viscoelasticity of domain-patterned FnHm Langmuir monolayers by applying periodic shear stresses. Remarkably, we found the formation of two-dimensional gels even at zero surface pressure. These monolayers are predominantly elastic, which is unprecedented for surfactants, exhibiting gelation only at high surface pressures. Systematic variation of the hydrocarbon (n=8; m=14, 16, 18, 20) and fluorocarbon (n=8, 10, 12; m=16) block lengths demonstrated that subtle changes in the block length ratio significantly alter the mechanics of two-dimensional gels across one order of magnitude. These findings open perspectives for the fabrication of two-dimensional gels with tuneable viscoelasticity via self-assembly of mesoscale, low-molecular-weight materials.